2018
DOI: 10.21873/anticanres.12945
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal and Systemic Chemotherapy for Patients with Gastric Cancer with Peritoneal Metastasis: A Phase II Trial

Abstract: Aim: To conduct a phase II study of single intraperitoneal (i.p.) administration of paclitaxel followed by paclitaxel, cisplatin, and S-1 (PCS) chemotherapy for patients with gastric cancer with peritoneal metastasis (PM). Patients and Methods: Staging laparotomy was performed to confirm PM. Initially, patients received i.p. paclitaxel. Beginning 7 days later, PCS was given every 3 weeks followed by second-look laparoscopy. Primary and secondary endpoints were the overall survival (OS) rate, and response rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Although many methods have been developed to conquer the peritoneal metastasis, such as hyperthermic intraperitoneal chemotherapy (HIPEC) (Yarema et al, 2019), pressurized intraperitoneal erosol chemotherapy (PIPAC) (Sgarbura et al, 2019), the outcome of GC with peritoneal metastasis is still unsatisfied. Intraperitoneal (IP) infusion of chemotherapy drugs offers an attempt to expose cancer cells to anti-cancer drugs at high drug concentrations with minimal systemic toxic effects (Shinkai et al, 2018), but implantation of the port may cause some complications. Yang et al reported that 22.9% patients experienced port complications, including subcutaneous liquid accumulation, infection, port rotation, inflow obstruction, and even subcutaneous metastasis (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although many methods have been developed to conquer the peritoneal metastasis, such as hyperthermic intraperitoneal chemotherapy (HIPEC) (Yarema et al, 2019), pressurized intraperitoneal erosol chemotherapy (PIPAC) (Sgarbura et al, 2019), the outcome of GC with peritoneal metastasis is still unsatisfied. Intraperitoneal (IP) infusion of chemotherapy drugs offers an attempt to expose cancer cells to anti-cancer drugs at high drug concentrations with minimal systemic toxic effects (Shinkai et al, 2018), but implantation of the port may cause some complications. Yang et al reported that 22.9% patients experienced port complications, including subcutaneous liquid accumulation, infection, port rotation, inflow obstruction, and even subcutaneous metastasis (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous chemotherapy was found to neither significantly lower the rate of peritoneal recurrence nor improve prognosis for patients with peritoneal gastric cancer recurrence. 6,12 It is thus urgent to establish treatment methods utilizing efficacious drugs. Due to the plasma-peritoneal barrier, most intravenous chemotherapeutic agents do not remain in sufficient contact with lesions.…”
Section: Discussionmentioning
confidence: 99%
“…13 Compared with intravenous chemotherapy, HIPEC has significant advantagesnotably the relative ease of attaining higher drug concentrations and a lower incidence of side effectswith proven beneficial effects in the treatment of gastric, colorectal, ovarian and other cancers. 6,[14][15][16] To date, a number of studies have confirmed the advantages of cytoreductive surgery (CRS) in combination with HIPEC for gastric cancer treatment. Cisplatin combined with 5-fluorouracil and mitomycin C has been the most widely studied HIPEC regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective of this study was to demonstrate that OS rate of patients treated with D-SOX was superior to that of patients treated with DOS. On the basis of previous research results [ 6 , 7 ], we assume that the 1-year OS rate of D-SOX and DOS are 75% and 50%, respectively. According to Lachin-Foulkes method (PASS 11.0, NCSS, USA), one-sided log-rank test was adopted with α of 0.05, 90% power, and 5.0% loss, and the target sample size was set at 78 patients.…”
Section: Methodsmentioning
confidence: 99%